Reduced Cortical Thickness in Schizophrenia and Schizotypal Disorder - Takayanagi, Yoichiro; Sasabayashi, Daiki; Takahashi, Tsutomu; Furuichi, Atsushi; Kido, Mikio; Nishikawa, Yumiko; Nakamura, Mihoko; Noguchi, Kyo; Suzuki, Michio (Schizophrenia bulletin, 2020)
Abstract Schizotypal disorder is characterized by odd behavior and attenuated forms of schizophrenic features without the manifestation of overt and sustained psychoses. Past studies suggest that schizotypal disorder shares biological and psychological commonalties with schizophrenia. Structural magnetic resonance imaging (MRI) studies have demonstrated both common and distinct regional gray matter changes between schizophrenia and schizotypal disorder. However, no study has compared cortical thickness, which is thought to be a specific indicator of cortical atrophy, between schizophrenia and schizotypal disorder. The subjects consisted of 102 schizophrenia and 46 schizotypal disorder patients who met the International Classification of Diseases, 10th edition criteria and 79 gender- and age-matched healthy controls. Each participant underwent a T1-weighted 3-D MRI scan using a 1.5-Tesla scanner. Cortical thickness was estimated using FreeSurfer. Consistent with previous studies, schizophrenia patients exhibited wide-spread cortical thinning predominantly in the frontal and temporal regions as compared with healthy subjects. Patients with schizotypal disorder had a significantly reduced cortical thickness in the left fusiform and parahippocampal gyri, right medial superior frontal gyrus, right inferior frontal gyrus, and right medial orbitofrontal cortex as compared with healthy controls. Schizophrenia patients had thinner cortices in the left precentral and paracentral gyri than those with schizotypal disorder. Common cortical thinning patterns observed in schizophrenia and schizotypal disorder patients may be associated with vulnerability to psychosis. Our results also suggest that distinct cortical changes in schizophrenia and schizotypal disorder may be associated with the differences in the manifestation of clinical symptoms among these disorders.